BIAS GENDER DALAM BAHASA INDONESIA (Gender Bias in Indonesian) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research is focused on the use of gender-biased terms in Indone¬sian among Javanese and outer Javanese society. The research has four objec¬tives: 1) to describe the forms of language units in gender-biased terms in Indonesian, 2) to describe the manifestation of gender bias in the forms of Indonesian language units, 3) to describe the gender-biased view of Indone¬sian speech community. The research can be included into descriptive-quali¬tative one by using the basic concept of triangulation between data, method, and technique. The data are Indonesian words, phrases, and clauses which are assumed as gender bias. The data are gained by using observation method (metode simak) and its basic technique, tapping (teknik sadap) and its advanced techniques, taking notes (teknik catat). In this case, Standard Indonesian Dic¬tionary (Kamus Besar Bahasa Indonesia), books, newspaper, and magazines are used. Then, those are confirmed with questionnaire as secondary data. The research has been done among Javanese and outer Javanese society that consists of 20 respondents from Java (5 men, 5 women and outer Java (5 men, 5 women). The result of the research shows that there are gender-biased terms in Indonesian can be classified into some levels, i.e. phonemes, morphemes, words, phrases, and clauses. Besides, gender bias manifests in Indonesian in the forms of: 1) the use of generic reference